Implementando segurança nas redes de comunicação através de VPN na internet: um estudo de viabilidade - Simões, Daniel Augusto (2013)
With the objective of demonstrating the feasibility of implementing VPN security in communication networks, this study used bibliographic research and concluded that VPN presents major economic and technical benefits applied nowadays. The share of its contributions in the development of new technologies and performance enhancement regarding security over the Internet as organization management tool with its innumerous services offered is a key factor. As for the security achieved, it was verified that the encryption algorithms as well as specific protocols generate major obstacle to invaders. VPN meets the criteria of security in relation to the integrity, confidentiality of information transmitted, as well as, authentication and access control, allowing greater trust on the part of companies that adopt this solution. They are therefore increasingly researched and adopted by corporations, whether private or governmental, in several systems and computing environments.